Multilayered silica-biopolymer nanocapsules with a hydrophobic core and a hydrophilic tunable shell thickness. Issue 16 (11th April 2016) - Vecchione, Raffaele; Luciani, Giuseppina; Calcagno, Vincenzo; Jakhmola, Anshuman; Silvestri, Brigida; Guarnieri, Daniela; Belli, Valentina; Costantini, Aniello; Netti, Paolo A.
Abstract : We provide a strategy to design an engineered nanocarrier system based on an oil-core/hybrid polymer/silica-shell with multifunctional and multicompartment features. Abstract : Stable, biocompatible, multifunctional and multicompartment nanocarriers are much needed in the field of nanomedicine. Here, we report a simple, novel strategy to design an engineered nanocarrier system featuring an oil-core/hybrid polymer/silica-shell. Silica shells with a tunable thickness were grown in situ, directly around a highly mono-disperse and stable oil-in-water emulsion system, stabilized by a double bio-functional polyelectrolyte heparin/chitosan layer. Such silica showed a complete degradation in a physiological medium (SBF) in a time frame of three days. Moreover, the outer silica shell was coated with polyethyleneglycol (PEG) in order to confer antifouling properties to the final nanocapsule. The outer silica layer combined its properties (it is an optimal bio-interface for bio-conjugations and for the embedding of hydrophilic drugs in the porous structure) with the capability to stabilize the oil core for the confinement of high payloads of lipophilic tracers ( e.g. CdSe quantum dots, Nile Red) and drugs. In addition, polymer layers – besides conferring stability to the emulsion while building the silica shell – can be independently exploited if suitably functionalized, as demonstrated by conjugating chitosan with fluorescein isothiocyanate. Such numerous features in a single nanocarrier system make it very intriguing as a multifunctional platform for smart diagnosis and therapy.